PERSPEKTIF TRADISIONAL MENGENAI SEJARAH PENGHIMPUNAN AL-QUR’AN - Rofiq, Ahmad Choirul (IAIN Ponorogo, 2012)
Abstrak: There are many scholars, both are Muslim and non-Muslim, who perform the study on the collection of the Quran with their different perspectives. Usually the muslim perspective is called the insider perspective or the traditionalist perspective, whereas the non-muslim perspective is considered as the outsider perspective or the revisionist perspective. Every perspective must avoid its claim of truth. According to the traditionalist perspective, the term of “jam‘ al-Qur’ân” means to memorize and to write the Quran. In the era of prophet Muhammad, the Quran was memorized and written thoroughly. After the death af Muhammad, the Quran was collected and bound as one by the order of Abû Bakr with a rigid procedure. This valuable policy was led by Zayd bin Tsâbit since ‘Umar bin al-Khaththâb suggested it to Abû Bakr because many readers of Quran were martyred on Yamamah. Then the Quran was standarized in the era of ‘Utsmân ibn ‘Affân because of many differences of Quranic reading, and accomplished by the team composed of Zayd bin Tsâbit, Sa’îd bin al-Âsh, ’Abd Allâh bin al-Zubayr, and ’Abd al-Rahmân bin al-Hârits. From that time, the writing of the Quran was completed by following generation to make the reading of the Quran easier. Pembahasan sejarah penghimpunan al-Qur’an menjadi perhatian para cendekiawan Muslim maupun non-Muslim. Biasanya perspektif tradisional identik dengan kaum Muslimin, sedangkan perspektif revisionis identik dengan masyarakat non-Muslim. Claim of truth dari setiap kelompok harus dihindari dalam mengkaji al-Qur’an. Dalam perspektif tradisional, istilah penghimpunan al-Qur’an (jam’ al-Qur’ân) berarti menghafalkan dan menuliskan al-Qur’an. Pada masa Nabi penghafalan dan pencatatan al-Qur’an sangat diperhatikan. Pada masa Abû Bakr, atas inisiatif ‘Umar bin al-Khaththâb, dilakukan pembukuan al-Qur’an yang dilaksanakan oleh Zayd bin Tsâbit. Motivasi penghimpunan al-Qur’an dikarenakan banyaknya penghafal al-Qur’an yang gugur selama perang Yamamah. Pelaksanaan pembukuan dilakukan sekitar satu tahun dengan berpegangan secara ketat pada hafalan, tulisan dan kesaksian dari para shahabat, sehingga kemutawatirannya terjamin. Pada masa ‘Utsmân, penyalinan dan pembakuan al-Qur’an karena terjadinya perselisihan cara membaca al-Qur’an yang berbeda-beda. Tim pelaksana pembakuan al-Qur’an terdiri dari Zayd bin Tsâbit, Sa’îd bin al-Âsh, ’Abd Allâh bin al-Zubayr, dan ’Abd al-Rahmân bin al-Hârits. Pada perkembangan berikutnya, dilakukan penyempurnaan tulisan al-Qur’an karena masih dijumpainya kesulitan dalam membaca al-Qur’an. Kata kunci: al-Qur’an, penghimpunan, perspektif tradisional, perspektif revisionis